2023
DOI: 10.1097/tme.0000000000000473
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbance and Occupational Fatigue in Emergency Nurses of Public Hospitals in Greece

Ioannis Kasimis,
Panteleimon Perdikaris,
Varvara Boutopoulou
et al.

Abstract: The emergency department (ED) is a stressful workplace for nurses, due to heavy workload and work shifts, which affect sleep quality, causing occupational fatigue. As a result, nurses burn out and turn over and quality of care is impaired. The aim of this study was to investigate sleep disturbance (SD) and occupational fatigue (OF) in emergency nurses of public hospitals in Greece. This descriptive cross-sectional study was conducted in the ED of tertiary public hospitals in Greece from September 2019 to Octob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Research has found that sleep quality is one of the independent predictors of fatigue levels among nurses ( 3 ). Nurses with sleep disorders are 2.9 times more likely to experience occupational fatigue ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research has found that sleep quality is one of the independent predictors of fatigue levels among nurses ( 3 ). Nurses with sleep disorders are 2.9 times more likely to experience occupational fatigue ( 4 ).…”
Section: Introductionmentioning
confidence: 99%